Parametric study and CFD simulation of a heat-driven adsorber for an air-conditioning system employing activated carbon - Harunal Rejan, Ramji (Universiti Malaysia Sarawak (UNIMAS), 2014)
Adsorption cooling systems powered by waste heat or solar heat can help to reduce the use of ozone depletion substances, such as chlorofluorocarbons (CFCs) and hydrochlorofluorocarbons (HCFCs). In this research work, a CFD simulation works were conducted on a prototype adsorption air-conditioning system powered by waste heat that was successfully tested in laboratory. The aim is to measure the system performance of the adsorption cooling and verify the results with experimental works.